Self-Management Behaviors of Diabetes Control Among Diabetic Patients in Indonesia (International Journal of Studies in Nursing, 2021)
Aims: This study was conducted to explore the behaviors of self-management of Indonesian diabetes patients on Diabetes (DM) control and health promotion. Methods: Grounded theory was applied to explore the health self-management, by used In-depth interview. Results: The study takes place in the community and health care center, by interviewed 20 respondents, to explain the health self-management behaviors. We found out 5 main themes including: Self-regularly take medication to control DM; Manage daily exercise activity in controlling DM; Manage my food and diet intake is necessary; Monitor blood sugar is the important part of DM control and; Monitor the hypo/hyperglycemia symptoms. Conclusion: The healthy self-management behaviors need to be improved to enhance the motivation and self-care skills among diabetic patients. Although, the disease management of DM patients may be affected by the environment, culture, and life experience. The results revealed that diabetic patients have multiple DM self-management unique attitudes and behaviors towards diabetes disease.